2016
DOI: 10.1007/s11051-016-3572-1
|View full text |Cite
|
Sign up to set email alerts
|

Graphene enterprise: mapping innovation and business development in a strategic emerging technology

Abstract: This paper explores enterprise development and commercialization in the field of graphene. Firm characteristics and relationships, value chain positioning, and factors associated with product entry are examined for a set of 65 graphene-oriented small and medium-sized enterprises located in 16 different countries. As well as secondary sources and bibliometric methods to profile developments in graphene, we use computerized data mining and analytical techniques, including cluster and regression modeling, to iden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
26
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(28 citation statements)
references
References 22 publications
2
26
0
Order By: Relevance
“…The first stage of graphene manufacturing could be the most critical in the value chain, since a single breakthrough induced by a large‐scale production method can fuel tremendous growth in the markets. According to the IDTechEx's market forecast, the market for graphene material would grow from ≈20 million in 2014 to ≈390 million in 2020 . In particular, the graphene industry has been developing rapidly in China.…”
Section: Techniques Utilized For Graphene Exfoliation and Dispersionmentioning
confidence: 99%
See 1 more Smart Citation
“…The first stage of graphene manufacturing could be the most critical in the value chain, since a single breakthrough induced by a large‐scale production method can fuel tremendous growth in the markets. According to the IDTechEx's market forecast, the market for graphene material would grow from ≈20 million in 2014 to ≈390 million in 2020 . In particular, the graphene industry has been developing rapidly in China.…”
Section: Techniques Utilized For Graphene Exfoliation and Dispersionmentioning
confidence: 99%
“…Angstron Materials in the US and Thomas Swan in the UK are two representative manufacturers . In 2015, Graphene Tracker reported that more than 60 companies worldwide were involved in graphene related activities; of these companies, around 30 were producing graphene, 20 supplying graphene‐based materials or devices, 6 making CVD or characterization equipment, and a dozen developing advanced graphene components and end products …”
Section: Techniques Utilized For Graphene Exfoliation and Dispersionmentioning
confidence: 99%
“…Although we relied on Scopus in this case, it would be desirable for future efforts to add/complement data from sources such as WoS, patent databases (USPTO, SP@ CENET, PATENTSCOPE, DWPI, and WIPO Gold), and specialized databases such as Chemical Abstracts Services, along with Web Content Mining techniques (Shapira et al, 2016). It would also be very interesting to replicate this work using other tools such as CiteSpace (Chen, 2004) or SciMAT (Cobo et al, 2012), to see and compare the different perspectives that these tools can bring into view.…”
Section: Limitations and Future Researchmentioning
confidence: 99%
“…Within the framework of carbonbased materials, however, this 2-D material suddenly aroused the attention of scientists (Lv et al, 2011). With the experimental discovery of graphene by Novoselov et al (2004), a rapidly growing stream of scientific literature became fertile land for bibliometric studies: Barth and Marx (2008), Wan and Pan (2010), Shapira et al (2010), Lv et al (2011), Munoz-Sandoval (2014), Small et al (2014), Terekhov (2015), Klincewicz (2016), and Shapira et al (2016).…”
mentioning
confidence: 99%
“…New energy industry: Lithium-ion battery; Supercapacitor; Solar cell Electronics industry: Flexible display device; Sensor Composite materials industry: Electrical conductivity composite material; Heat conductivity composite material; Reinforcement material Biomedical industry: Drug carrier; Gene therapy; Biological detection Environmental protection industry: Sea water desalination; Sewage disposal Since the year following the 2010 Nobel Prize in Physics award for earlier pioneering work on graphene, there has been rapid growth in global graphene technological innovative management [14]. Substantial efforts and governmental funding from many countries or regions, such as the U.S., China, the U.K, the EU, Korea, and Japan, have been focused towards graphene research and development.…”
Section: Downstream Industrymentioning
confidence: 99%